TORTOR HUSIP-HUSIP DALAM UPACARA KEMATIAN SAURMATUA PADA MASYARAKAT BATAK TOBA KAJIAN KOMUNIKASI NON VERBAL - Yuli M Sidabutar (Universitas Negeri Medan, 2017)
This study aims to find out how non-verbal communication of Tortor Husip-husip in Batak Toba society. The population in this study are some of the traditional leaders Batak Toba society in Simanindo district, some of the artists who know about Tortor Husip-husip and the actors (citizens) who are involved as performer Tortor-husip Husip. The sample is also customary prominent figure, artists, and actors involved in Tortor Husip-husip. The method is used descriptive qualitative method. To complete the data in this study, the research conducted field observations, video, interviews and also documentation. The results of the data collected can be seen in non-verbal communication of Tortor Husip-husip in Batak Toba society, which is not only as a dance performed in ceremonies of death Batak Toba, but also can serve as a medium of communication and symbolic systems. The uniqueness and characteristic of this tortor are gotten in Husip-husip which has meaning how expressing of whispering, hopeful and prayers to those who have Saurmatua. As a medium of non-verbal communication can be seen from the gesture. The dancers are not only get dance as usual, but there are non-verbal messages will be conveyed through by gesture in Tortor Husip-Husip. The form of non-verbal communication in Tortor Husip-husip is symbolized by keep nodding head with body position leaning forward and whispering with a corpse. Gondang Bolon as the traditional music is used in this ceremonial celebrating. It contains sarune, taganing, gordang, ogung and hesek. The Non-verbal messages will be submitted to each community must be respecting to parents. And the Tortor Husip-husip is one of final tribute and delivering of the prayer, hope, gratitude and apology to the parents who have saurmatua.